Natural products as a source of Coronavirus entry inhibitors - Szabó, Dávid; Crowe, Andrew; Mamotte, Cyril; Strappe, Padraig (Frontiers in Cellular and Infection Microbiology, 2024)
The COVID-19 pandemic has had a significant and lasting impact on the world. Four years on, despite the existence of effective vaccines, the continuous emergence of new SARS-CoV-2 variants remains a challenge for long-term immunity. Additionally, there remain few purpose-built antivirals to protect individuals at risk of severe disease in the event of future coronavirus outbreaks. A promising mechanism of action for novel coronavirus antivirals is the inhibition of viral entry. To facilitate entry, the coronavirus spike glycoprotein interacts with angiotensin converting enzyme 2 (ACE2) on respiratory epithelial cells. Blocking this interaction and consequently viral replication may be an effective strategy for treating infection, however further research is needed to better characterize candidate molecules with antiviral activity before progressing to animal studies and clinical trials. In general, antiviral drugs are developed from purely synthetic compounds or synthetic derivatives of natural products such as plant secondary metabolites. While the former is often favored due to the higher specificity afforded by rational drug design, natural products offer several unique advantages that make them worthy of further study including diverse bioactivity and the ability to work synergistically with other drugs. Accordingly, there has recently been a renewed interest in natural product-derived antivirals in the wake of the COVID-19 pandemic. This review provides a summary of recent research into coronavirus entry inhibitors, with a focus on natural compounds derived from plants, honey, and marine sponges.